#STOPASIANHATE: Donald Trump's Political Propaganda Against Asian Racism in the United States - Arofah Minasari; Dini Nurkhasanah; Rahmannisa Kirana; Salma Dewi; Santi Pratiwi (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
During the Covid-19 pandemic, the issue of racism became a hot topic discussed by the world community, especially in the United States. The bustle of the #STOPASIANHATE hashtag illustrates that the issue of racism is attracting the attention of the world community massively. The emergence of this hashtag was triggered by one of the political propagandas of the Former President of the United States, Donald Trump, through his tweet stating that the Covid-19 virus was the